Reward responses to vicarious feeding depend on BMI - Järvinen, Lili (My University, 2024)
Eating is inherently social for humans. Yet, most neuroimaging studies of appetite and food-induced reward have focused on studying brain responses to food intake or viewing pictures of food alone. In this study functional magnetic resonance imaging (fMRI) is used to measure haemodynamic responses to “vicarious” feeding. The subjects (n=97) viewed series of short videos representing naturalistic episodes of social eating intermixed with videos without feeding / appetite related content. Viewing the vicarious feeding (versus control) videos activated motor and premotor cortices, thalamus, and dorsolateral prefrontal cortices, consistent with somatomotor and affective engagement. Responses to the feeding videos were also downregulated as a function of the participants’ BMI. Altogether these results suggest that seeing others eating engages the corresponding motor and affective programs in the viewers’ brain, potentially increasing appetite and promoting mutual feeding.
Keywords: lihavuus, fMRI, syöminen